Debunking the Illusion of Adolescents: Analyzing the Relationship between Personal Fable and Smoking Behavior in Adolescents - Shalsabilla, Riski Yanti; Hurriyati, Dwi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Smoking behavior has become a hot topic of conversation because it is very common, especially among teenagers. Smoking behavior can have negative impacts such as health, social, psychological and economic problems. It can trigger criminal acts for smokers who do not yet have an income such as teenagers. This study aims to reveal the relationship between personal fable and smoking behavior in junior high school male teenagers who smoke. The method in this study uses quantitative correlation with 110 junior high school male teenagers who smoke as research subjects, the research sample was taken using a simple random sampling technique with a 5% error rate, This study uses a measuring instrument from a smoking behavior scale with a total of 49 valid items with a validity value of 0.325 and a reliability value of 0.908 and a personal fable scale with a total of 50 valid items with a validity value of 0.330 and a reliability value of 0.911. The results of this study indicate a significant positive correlation between personal fable and smoking behavior in junior high school male teenagers who smoke at a level of 35%. The practical implication of this study is that personal fable has an effective role in triggering smoking behavior in junior high school-level male adolescents, so adolescents are advised to be smart in making decisions related to behavior and socializing because the influence of the environment and peers also plays a major role in the behaviors that adolescents develop.Perilaku merokok menjadi marak pembicaraan karena sudah sangat lumrah dilakukan terlebih di kalangan remaja. Perilaku merokok dapat memberikan dampak negatif seperti permasalahan kesehatan, sosial, psikologis dan ekonomi. Mampu terpicunya tindakan kriminal bagi pelaku merokok yang belum memiliki penghasilan seperti kalangan remaja. Penelitian ini bertujuan untuk mengungkap hubungan yang ada dari personal fable dengan perilaku merokok pada remaja laki-laki setingkat SMP yang merokok. Metode dalam penelitian ini menggunakan kuantitatif korelasi dengan 110 remaja laki-laki setingkat SMP yang merokok sebagai subjek penelitian, sampel peneitian diambil dengan teknik simple random sampling dengan taraf kesalahan 5%, Penelitian ini menggunakan alat ukur dari skala perilaku merokok dengan jumlah 49 aitem valid dengan nilai validitas 0.325 dan nilai reliabilitas 0.908 dan skala personal fable dengan jumlah 50 aitem valid dengan nilai validitas 0.330 dan nilai reliabilitas 0.911. Hasil penelitian ini menunjukkan korelasi positif yang signifikan antara personal fable dengan perilaku merokok pada remaja laki-laki setingkat SMP yang merokok dengan taraf 35%. Implikasi praktis dalam penelitian ini adalah personal fable memiliki peran efektif dalam memunculkan perilaku merokok remaja laki-laki setingkat SMP, sehingga remaja disarankan dapat cerdas dalam mengambil keputusan terkait dengan perilaku dan bersosial karena pengaruh dari lingkungan dan teman sebaya juga berperan besar bagi perilaku-perilaku yang ditimbulkan remaja.